The Effect of Methanol Extract of Leaves of Hibiscus Rosa-Sinensis L. against Methicillin-Resistant Staphylococcus Aureus (MRSA) - Mona Fathia; Risa Nursanty; Nurdin Saidi (Biologi Edukasi: Jurnal Ilmiah Pendidikan Biologi, 2015)
This study was aimed to determine the effect of the methanol extract against bacteria Methicillin Resistant Staphylococcus aureus (MRSA) and to measure its inhibition capacity. Phytochemical test and extraction were conducted at the Research Laboratory of Chemistry Department, Faculty of Mathematics and Natural Sciences (MIPA). Antibacterial test was done at the Laboratory of Microbiology Department of Biological Science, University of  Syiah Kuala. The samples used leaves of H. rosa-sinensis collected from Gampong Sektor Timur, Darussalam.This study used completely randomized design (CRD) with five treatements and three replications namely; negative control using the solvent, extract test with  concentrations 0.2 g / mL, 0.3 g / mL, 0.4 g / mL, and  positive control using 30 µg linezolid. Phytochemical test showed that the fresh samples contain alkaloids, terpenoids, steroids, and flavonoids, while the methanol extract contains alkaloids and flavonoids. Antibacterial test showed that the methanol extract have inhibited MRSA bacterial growth, with the average of inhibition zone was 15.90 mm at the concentration of 0.4 g / mL.